Analisis Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Susu Cair Uht Ultramilk Di Jabodetabek - Agnes Indri Astuti (Lembaga Pengembangan Kinerja Dosen, 2023)
Industry competition is growing rapidly and swirling in various markets. There are a lot of industries in Indonesia, from small to large. One of them is the Milk UHT Ultramilk. Therefore, this study aims to understand the impact of the price and quality of products on the purchase decision for the brand is the UHT Ultramillk Liquid Milk in Jabodetabek. This research method uses quantitative descriptive research with Convenience sampling techniques. The population of this study is comprised of consumers who have consumed or purchased the UHT Ultramilk Liquid Milk Drink brand, with the number of samples taken reaching as many as 120 respondents. The data analysis methods in this study are validity tests, rehabilitation tests, classical assumption tests, double linear regression analysis, and hypothesis tests (f test, T test, and determination R2). The results of this study show that the price and quality of the product have a positive and significant impact, both partially and simultaneously, on the purchase decision.